IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK DALAM MEMBENTUK SIKAP TAWADHU’ SANTRIWATI DI PONDOK PESANTREN AL-KHAIR PONOROGO - Intan Dina Wijaya; Happy Susanto; Muh Tajab (PT. Hasba Edukasi Mandiri, 2025)
As time progresses, more and more challenges are faced, such as the decline of morals in children. It's happens because of the lack of knowledge of moral education. Moral Creed Education is a very important education that must be given to students. To address this, one of the Islamic education institutions, namely the Al-Khair Islamic Boarding School, uses Aqidah Akhlak education as a means of forming an attitude of tawadhu' for female students. This research discusses the implementation of Aqidah Akhlak learning, the results of the implementation of learning Aqidah Akhlak, as well as supporting and inhibiting factors in the implementation of Aqidah Akhlak learning to form an attitude of tawadhu' among female students at the Al-Khair Islamic Boarding School. This research uses a qualitative descriptive method by utilizing qualitative data and then explaining it descriptively. Data collection techniques use interviews, observation, and documentation. This research resulted in an explanation of the process of educating Santriwati's tawadhu's attitudes in Islamic boarding schools through strategies and several methods, including: lectures, telling stories, habituation, giving examples, giving advice, and punishment. The impact of these methods is that female students at the Al-Khair Islamic boarding school have good morals, behave politely towards older people, smile, greet when they meet Ustadz or Ustadzah, act tawadhu', and obey the rules.